(untitled) (Revista Espinhaço, 2025)
Although diamonds from the Diamantina district have been known and studied since the 18th century, their genesis, associated mantle processes and environmental context of the rise of kimberlites are still unknown. Furthermore, the nature and source area of these diamonds has been the subject of intense scientific debate for decades. Therefore, in order to add knowledge about the origin and history of diamonds from the Serra do Espinhaço diamond province, samples of diamonds from São João da Chapada and the Jequitinhonha River areas were studied in this work. The surface and infrared spectral characteristics of the studied crystals and the analysis of their mineral inclusions suggest that the sublithospheric (hence, cratonic) Jequitinhonha River diamonds crystallized in the peridotite mantle, since the presence of forsterite inclusion implies crystallization at temperatures of 1170 ºC and pressure of 65 kbar. Furthermore, the presence of flat-bottomed trigons indicates that these diamonds reacted with H2O-rich fluids during the final stages of the kimberlite emplacement. The abundant presence of ruts in São João da Chapada diamonds indicates crystallization conditions in highly oxidized volcaniclastic kimberlite, at temperatures of 1040 ºC. The diamondiferous ruditic rocks of the Sopa-Brumadinho Formation were deposited around 1.7 Ga, therefore, the minimum age of the kimberlitic event. As cratonic diamonds reside for a prolonged period in the lithospheric mantle, the crystallization of diamonds from southern Espinhaço Mountain Range during the Neoarchean period ( 3.0 Ga) is suggested.